Don't blink [compact disc, unabridged] : a novel - Patterson, James, 1947- (Hachette Audio, 2010)
When an assassin successfully hits a notorious mob lawyer at Lombardo's Steak House, the other patrons in the restaurant are left stunned. Among them is reporter Nick Daniels, whose dream interview with a baseball legend is ruined. As a key witness to the murder, Nick finds himself wanted by most of New York's major political players. However, when he attempts to investigate the case himself, Nick discovers that he might have stumbled upon an international Mafia war.